Formas de ser professor na EaD: práticas que contam de si - Szulczewski, Deise Maria (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation has as its objective problematize the development of the professor who works or have already worked at distance education programs. The research is based on the ideas of Michel Foucault and it is developed into the concepts of political governmentality, and its constituents: government and subjectivation. Interviews with professors who work or have already worked at distance education programs have been used as a research material. The reflections developed are divided into four chapters and allow us to see the actions of the State, as well as the intellectual theorizations in the field of Education, and the actions of professors on themselves in the development of distance education professionals. It was possible to state through the research a series of other things. First the technological education courses constitute a necessary aleturgia in order to make professors feel capable of working at this education method. Secondly there is a discursive net acting on the professors that raises difficulties in innovating this teaching field due to its trivialization caused by onsite education. Finally due to the influence of the truths that constitute the onsite education, professors have been acting on themselves demanding and outlining the distance education programs in the same the way they have guided and prepared the onsite education programs. This research intends to contribute to the discussions about the Education field disposing of problematizations that are able to guide actions that generate other ways of training professors that will work at distance education.
Keywords: Professor; EaD; Governamentalidade; Subjetivação; Distance Education Professor; Governmentality; Subjectivation; ACCNPQ::Ciências Humanas::Educação